Isolation and characterization of lignocellulolytic microbes from oil palm empty fruit bunches (EFB) - Ariana, Ariana; Candra, Krishna P. (Centre for Science and Technology, IAIN Surakarta, 2017)
Oil palm empty fruit bunches (EFB) is one of the major by-products of palm oil production. This lignocellulosic biomass is commonly used as a fertilizer at oil palm plantations. Unfortunately, the composting process of EFB is very slow. This study aimed to identify potential lignocellulosic microbes isolated from EFB. This information is essential for improving EFB biodegradation process by reducing the decomposition time. Samples of approximately 6, 12, and 24-month-old EFB were obtained from two palm oil mills in East Kalimantan, Indonesia. The isolation of lignocellulytic microbes utilized selective medium cellulose congo red agar (CCRA) while its characterization used lignin agar (LgA) and oil palm empty fruit bunches agar (EFBCRA). As much as 430 isolates were successfully collected and 12 of them exhibited promising capability to synthesize lignocellulolytic enzyme, the key for FEB degradation.